2020
DOI: 10.1097/meg.0000000000001872
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic therapy + β-blocker vs. covered transjugular intrahepatic portosystemic shunt for prevention of variceal rebleeding in cirrhotic patients with hepatic venous pressure gradient ≥16 mmHg

Abstract: Background and objective Currently, monitoring hepatic venous pressure gradient (HVPG) have been proved to be the best predictor for the risk of variceal bleeding. We performed the study to evaluate the effect of endoscopic therapy + β-blocker vs. covered transjugular intrahepatic portosystemic shunt (TIPS) for the prevention of variceal rebleeding in cirrhotic patients with HVPG ≥16 mmHg. Methods Consecutive cirrhotic patients with HVPG ≥16 mmHg treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Moreover, HVPG ≥ 20 mmHg has been a clinically effective predictor of early rebleeding [11] . In our previous study [12] , During a 1-year follow-up time, we concluded that covered TIPS was more effective than standard therapy in preventing rebleeding but that it did not improve survival.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, HVPG ≥ 20 mmHg has been a clinically effective predictor of early rebleeding [11] . In our previous study [12] , During a 1-year follow-up time, we concluded that covered TIPS was more effective than standard therapy in preventing rebleeding but that it did not improve survival.…”
Section: Introductionmentioning
confidence: 87%
“…Finally we included 184 patients in our study. Eighty-three of the 184 patients have been previously reported [12] . The prior article examined the effect of covered TIPS vs. endoscopic therapy+β-blockers in patients with HVPG≥16 mmHg at a 1-year follow-up, whereas in this study, which included all patients with HVPG≥10 mmHg, we report on the long-term outcome after covered TIPS therapy.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the procedures were completed by 2–3 experienced gastroenterology intervention doctors in this institution. The process of the TIPS procedure has been described in detail in previous articles ( 9 ). Briefly, the right or middle hepatic vein was catheterized using a transjugular venous approach with RUPS-100 (COOK; Indiana, United States) under local anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…It should be therefore reserved for select cases. 26 In the setting of bleeding esophageal varices, the ideal candidate for shunt placement within the first 3 days of presentation would have no history of hepatic encephalopathy, no history of heart failure or tricuspid valve regurgitation, no signs of sepsis, no pulmonary hypertension, and no significant coagulopathy.…”
Section: ■ Management Of Esophageal Varicesmentioning
confidence: 99%